FlowOptix : A Traffic Signal Control and Management System - Viraj Tapkir; Shubham Shinde; Mitesh Shetkar; Sonali Dalvi (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The innovation in the field of vehicles has led to the access of vehicles in high reach, thus increasing the number of vehicle counts. But this increase count has created a need of managing the congestion of vehicles on road in a more efficient way. The traditional system and approach of the traffic signal systems isn’t adequate enough to tackle the increasing congestion. The traditional system tends to be efficient where the count is sparse, as the density of vehicles on a particular side of road increases or if the traffic is comparatively larger on one side than other side in such case the approach fails. Hence, the introduced system redesigns the traffic signal system that is static switching to signal switching based on real-time traffic management. So, in this project the switching time of signal will be decided based on real time image detection with good accuracy in dense traffic. This practice can prove its most effectiveness in releasing the congested traffic at an efficient and faster rate.